Positioning patients for robotic‐assisted surgery: A qualitative study of operating room nurses' experiences - Benedikte Bjøro; Ingvild Ballestad; Tone Rustøen; Monica Hetlesæther Fosmark; Signe Berit Bentsen (Wiley, 2023)
Abstract Aim One of the challenges of robotic‐assisted surgery is related to positioning of the patient on the operating table. Technological developments place increased demands on operating room nurses' competence to prevent positioning injuries and ensuring care quality. Therefore, the aim of the present study was to describe operating room nurses' experiences when positioning the patients for robotic‐assisted surgery. Design A descriptive qualitative design. Methods Seven operating room nurses with experience in robotic‐assisted surgery were included at a university hospital. Data were obtained through individual interviews and analysed using qualitative content analysis. The Consolidated Criteria for Reporting Qualitative research COREQ checklist was used. Results We identified three categories, (a) patient positioning is challenging during robotic‐assisted surgery, (b) operating room nurses take responsibility for patient positioning during robotic‐assisted surgery, but teamwork is important and (c) operating room nurses aim to achieve safe patient positioning during robotic‐assisted surgery.